Decision Support System for The Acceptance of Medical Staff Using the Profile Matching Method at Mitra Sejati Hospital - Finna Handayani; Tarigan, Nera Mayana (Journal of Data Science, Technology, and Artificial Intelligence, 2024)
The Hospital is one of the healthcare referral centers that consistently provides comprehensive health services. One crucial factor influencing healthcare services is the professional, high-quality, and competent nursing staff. However, the assessment process for the acceptance of nursing medical staff at Mitra Sejati Hospital still relies on manual calculations. It is evident that many hospitals assess candidates based on their proximity to the nursing medical staff. Therefore, there is a significant need for a decision support system in the recruitment of medical staff. The method used in the recruitment of medical staff is the Profile Matching Method. The criteria used in this research are: 1) Highest Education. 2) Professional License (STR). 3) Basic Trauma Cardiac Life Support (BTCLS) certification. 4) Age. 5) Work Experience. This system is built by implementing the web-based Profile Matching Method with MySQL as its database. With the application of the Profile Matching Method in determining the acceptance of nursing medical staff, out of the 7 predetermined candidates, 4 candidates were accepted. They are Rusli Sako with a score of 4.82, Yusniar Lubis with a score of 4.52, DRS Mandir Sagala with a score of 3.98, and Suryadani with a score of 3.96.